PENERAPAN MEDIA BUKU SAKU DALAM MENINGKATKAN KEMAMPUAN MEMBACA PESERTA DIDIK KELAS II YP AR-RIDHA SIBIRU-BIRU - Andini, Dwi; Destini, Rita; Sukmawarti; Darwis, Umar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low reading ability of second-grade students of YP Ar-Ridha Sibiru-Biru in Indonesian language learning, which is partly caused by the lack of use of interesting learning media that are appropriate to the characteristics of students. This study aims to improve students' reading ability through the application of pocket book media in second-grade students of YP Ar-Ridha in the 2025/2026 academic year. This study uses the Classroom Action Research (CAR) method which is implemented in three cycles with the stages of planning, action implementation, observation, and reflection. Research data were collected through observation, tests, and documentation, then analyzed descriptively quantitatively with percentages. The indicator of research success is determined if classically 75% of students achieve the KKM score. The results of the study show that the application of pocket book media can improve students' reading ability. At the pre-cycle stage, student learning completeness only reached 31.25%. After the action was given, learning completeness increased to 50% in cycle I, 75% in cycle II, and 93.75% in cycle III. In addition, the average value of students' reading ability also increased, namely 70.68% in cycle I, 75.00% in cycle II, and 82.06% in cycle III. These results indicate that pocket books are effective in increasing students' interest, motivation, involvement, and reading ability in Indonesian language learning. Based on the results of the study, it can be concluded that the application of pocket books can improve the reading ability of class II students at YP Ar-Ridha Sibiru-Biru. Thus, pocket books can be used as an alternative effective learning media to improve the reading ability of elementary school students.